HUBUNGAN DISIPLIN BELAJAR DENGAN PRESTASI BELAJAR SISWA KELAS IV SDN KARAWACI 3 KOTA TANGERANG - Hilda Firliyansyah; Septy Nurfadhillah; Yeni Nuraeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is a relationship between learning discipline and learning achievement of fourth grade students. This study was conducted at SDN Karawaci 3, Tangerang City. The method used is a quantitative survey method. The sample in this study was all fourth grade students of SDN Karawaci 3, Tangerang City, totaling 48. Data collection techniques using questionnaires, data analysis using SPSS version 27. The results of the calculation of the values ​​of  and  then = 3,292> = 1.677, it can be concluded that  is rejected and is accepted at  = 0.406, meaning that learning discipline has a significant relationship with the learning achievement of fourth grade students of SDN Karawaci 3, Tangerang City.